KOMPARASI KINERJA USAHA TANI PADI SAWAH DENGAN MENGGUNAKAN BERBAGAI TIPE TRAKTOR - Paman, Ujang; Ati Prihatiningnur; Azharuddin (Fakultas Pertanian Universitas Janabadra, 2025)
Types of tractors used for tillage operations in paddy fields have developed in varius types with diffrent performances. The purpose of this study is to analysis the costs, yields, profit, and efficiency of rice farming and compare them with farms that employ four-wheel tractors, rotary tillers, and moldboard flows. A survey-based study was carried out in the Rengat Barat District of the Indragiri Hulu Regency from October 2022 to March 2023. A total of 70 farmers was chosen at random for samples; 20 of them used four-wheel traktor, 25 used rotary tillers, and 25 used moldboard flows. Data were obtained from primary and secondary data. The primary data were collected by personal interviews. The collected data were tabulated and then analized using simple matematic and different test. The results showed that the rice farming using four-wheel tractors was the best performnce in costs (IDR 7,198,530/ha/growing season)) and economic efficiency (1.69). The best performance in productivity (2.8 ton/ha/growing season)) and profit (IDR. 5,443,486/ha/growing season)) was found for the rice farmings used mouldboard flows. Based on difference test showed that the average of production costs, productivity, profit and eficiency significanly differed between rice farming used four-wheel tractors, power tillers and moulboard plows at the significant level of 5%. The findngs suggest that farmers must choose the best performnace of rice farming by using four-wheel tractors for a higher eficiency or mouldboard flows for getting more profit.